Mycobacterium vaccae Adaptation to Disinfectants and Hand Sanitisers, and Evaluation of Cross-Tolerance with Antimicrobials - Carla C. C. R. de Carvalho; Raquel Teixeira; Pedro Fernandes (MDPI AG, 2020)
Mycobacterium vaccae is being considered as an adjuvant to antituberculosis therapy, tested for the treatment of autoimmune diseases, and as an anti-depressive agent. This bacterium is ubiquitous in the environment and the widespread use of disinfectants and sanitisers may lead to its adaptation to these compounds. In the present study, M. vaccae cells adapted to these compounds mainly by making adjustments in their lipid composition and net surface charge. The modifications in the lipid composition led to changes in membrane permeability which resulted in increased tolerance towards levofloxacin, thioridazine, and omeprazole.